Narratives of loss: the impact of Covid-19 lockdown on experiences of loss, grief, and bereavement - Richard Egan; Lis Heath; Rhiannon Dew (CSIRO Publishing, 2022)
Introduction Restrictions imposed to eliminate the spread of the coronavirus disease 2019 (COVID-19) virus had significant implications on peoples' experiences of caring for family/whānau at the end of life, and on their own bereavement process. Aim This qualitative research explored the impact of COVID-19 lockdown restrictions on experiences of loss, grief and bereavement in Aotearoa New Zealand. Methods This qualitative narrative research used semi-structured interviews with 10 participants who experienced the loss of a loved one during Levels 3 or 4 lockdown in Aotearoa New Zealand (23 March-13 May 2020). Interviews were coded using NVivo software and inductive thematic analysis was used to evaluate the data. Results Results were grouped into three themes: death experience; mourning in isolation; and availability of support. These themes provide insight into the challenges and difficulties participants faced when they experienced the death of a loved one during a COVID-19 lockdown, and the impact of these restrictions on their experiences of grief and bereavement. Discussion The findings from this research suggest there is an increased risk of prolonged grief among those bereaved during lockdown. Primary care professionals need to be aware of this increased risk in order to identify need and provide access to bereavement support.